Robust structural and parametric optimization of systems of stabilization of ground moving objects - Сущенко, О.А. (Proceedings of National Aviation University (archive), 2009)
Features of the ground vehicle robust stabilizing system structure-parametric synthesis are analysed. Approaches to this problem solution are suggested. The simulation results are represented.